WORLD TRENDS IN THE AUTOMOTIVE INDUSTRY: LESSONS FOR THE DEVELOPMENT OF THE UKRAINIAN AUTOMOTIVE SECTOR IN THE ERA OF ECONOMIC GLOBALIZATION - DIDYK, Andriy; LAZAREV, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article demonstrates that the automotive industry is a significant component of the global economy due to its overall market volume, contribution to GDP, and the number of employed workers.The importance of the automotive industry has prompted an exploration of current global trends in the automotive industry. The trends identified include the development of 'green' technologies in the context of addressing climate change, the rise of 'green' protectionism, and the intensification of economic rivalry between China and Western countries. Other trends encompass the proliferation of autonomous vehicles based on the advancement of artificial intelligence technologies, the integration of cars into the broader network of connected devices within the Internet of Things and cloud technologies, the increased concentration of global value chains, the growth of the sharing economy, urbanization, and the development of urban transport. Furthermore, there is a heightened emphasis on the safety of vehicles, along with regulatory frameworks addressing these requirements. The emergence and development of individual flying devices as alternative modes of transportation are also noteworthy trends.With the aim of assessing the relevance of these trends for Ukraine and their implementation, manifestations of these trends in Ukraine have been evaluated. It has been shown that the most pronounced manifestations include the increased concentration of global value chains and urbanization along with the development of urban transport. To assess the prospects for further development of the examined trends in Ukraine, an evaluation of the readiness of the Ukrainian economy to implement these trends in the automotive industry is presented. The analysis reveals that the Ukrainian economy is most prepared for trends such as the development of 'green' technologies in the context of combating climate change and the growth of the sharing economy.It is shown that the trends in automotive engineering both present opportunities and pose threats to domestic car manufacturers. The composition of these opportunities and threats is outlined. Explored opportunities are mainly associated with the emergence of additional market segments, a stable demand pattern, and the creation of additional economic advantages. The presented threats are mostly linked to changes in demand structure and the insufficient competitiveness of Ukrainian automobile manufacturers in the global market.Factors limiting the opportunities of Ukrainian automotive manufacturers are identified, and the consequences of these factors are demonstrated, ultimately leading to the insufficient competitiveness of Ukrainian producers, an inability to scale production, and difficulties in technical upgrading.The results of the article are of interest for shaping the development of the automotive industry in Ukraine.
Keywords: trend; production of automobiles; globalization; "green technologies"; value chain; opportunities; threats; limiting factors